Kedudukan Hukum Ketetapan MPRS/MPR Sebelum dan Sesudah Perubahan UUD 1945 - Edy Asnawi (Faculty of Law Universitas Lancang Kuning, 2020)
Amendments to the 1945 Constitution have implications for changes in the power or institutional authority of the MPR which have an effect on the legal position of the MPRS / MPR decisions that were born, both before and after the amendments to the 1945 Constitution. For this reason, the method used is a normative juridical research method. The results show that in state administration practice as long as the 1945 Constitution comes into effect before the amendment is made, the wide scope of material content that is regulated is not only limited to matters specified in the 1945 Constitution. a kind of State administration stipulation (beschikking), MPR Decrees in the form of planning (GBHN), and MPR decrees such as policy regulations (beliedregels) in the field of state administration. After the amendment of the 1945 Constitution was made, the legal position of the MPR Decree became summarized, on the one hand the amendments to the articles of the 1945 Constitution and the provisions of Article 1 Additional Rules of the 1945 Constitution resulted in the loss of the MPR's authority to form MPR decrees (types of laws and regulations). regulating (regeling), because it no longer has a constitutional basis in the 1945 Constitution. But on the other hand, with the enactment of Law Number 12 of 2011 concerning the Establishment of Legislative Regulations, the legal position of the MPR Stipulation has come alive again as a form of statutory regulation with restrictions as referred to in the elucidation of Article 7 paragraph 1 letter b, namely the still valid MPRS / MPR Decrees as stipulated in the MPR Decree Number 1 / MPR / 2003.